Controlling the Shape of Anatase Nanocrystals for Enhanced Photocatalytic Reduction of CO2 to Methanol - Truong, Quang Duc; Hoa, Huu Thu; Vo, Dai-Viet N.; Le, Thanh Son (Royal Society of Chemistry, 2017)
Herein, we report a simple thermal-induced synthesis of pyramidal anatase TiO2 nanocrystals with exposed {101} and {001} facets with controlled shapes and truncated particles. Anatase phase of rod-like structures or truncated bipyramidal nanocrystals was prepared by tailoring the temperature or treatment time in a hydrothermal method using peroxotitanic acid as a precursor without using any shapecontrolling reagent. The presence of both {101} and {001} facets in the synthesized nanocrystals enhances the separation of electrons and holes and improves the photocatalytic reduction of CO2 to methanol.